Treatment of Ruptured Anterior Communicating Artery Aneurysms: Equipoise in the Endovascular Era?. Issue 4 (25th June 2015) - Moon, Karam; Levitt, Michael R.; Almefty, Rami O.; Nakaji, Peter; Albuquerque, Felipe C.; Zabramski, Joseph M.; McDougall, Cameron G.; Spetzler, Robert F.
Abstract: BACKGROUND: Ruptured anterior communicating artery (ACoA) aneurysms are heterogeneous intracranial aneurysms whose diverse morphological features influence treatment modality. OBJECTIVE: To compare clinical outcomes and complications of all ruptured ACoA aneurysms treated by clipping or coiling in a modern institutional trial. METHODS: All patients with ruptured ACoA aneurysms in the Barrow Ruptured Aneurysm Trial were included. Clinical follow-up at 1 and 3 years was analyzed; charts were reviewed for patient demographics, aneurysm characteristics, and in-hospital complications. RESULTS: This cohort included 130 patients (mean age, 52.5 years). Mean aneurysm size was 5.8 mm. Most aneurysm domes projected anteriorly (n = 52). After randomization and crossover, 91 ACoA aneurysms (70%) were clipped and 39 (30%) were coiled. Twenty-two patients (16.9%) initially randomized to coiling crossed over to clipping after evaluation. No patients crossed over from clipping to coiling. Characteristics precluding aneurysms from coiling included unfavorable dome-to-neck ratio, lesions difficult to access by catheter, and branch vessel involvement. Aneurysm size and dome projection were not significantly associated with treatment group, clinical outcome, or retreatment. No significant difference existed in clinical outcome (modified Rankin Scale scores) between groups at discharge or at 1-year or 3-year follow-up using as-treated and intention-to-treat analyses. Retreatment was performed in 3 clipped patients (2.3%) and 3 coiled patients (2.3%). CONCLUSION: Ruptured ACoA aneurysms, regardless of size and projection, were safely treated by both treatment modalities in a large-scale randomized clinical trial. Clinical outcomes and stroke rates did not differ significantly in as-treated or intention-to-treat analyses.